Smart Culture Village: Pelatihan Literasi Keuangan Koperasi Merah Putih, Inovasi Produk, dan Wisata Edukasi Cau Chocolate sebagai Penggerak Ekonomi Kreatif Desa - Anak Agung Gede Mahendra Kusuma; Putu Agus Gandi Griastana; Wayan Supada; I Ketut Suweca; Anak Agung Ananta Putra (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The community service activity conducted by the Management Economics Study Program in Kuwum Village, Marga District, Tabanan Regency aims to provide inspiration and efforts toward realizing a smart culture village through product innovation and Cau Chocolate educational tourism as a driver of the village’s creative economy. The activity was carried out on November 24-26, 2025, at the Kuwum Village Hall with a sharing and mentoring method for 30 participants. At the end of the program, participant satisfaction was measured through the distribution of questionnaires. The results of this community service activity indicate that the smart culture village initiative through Cau Chocolate product innovation and educational tourism as a driver of the creative economy was successfully implemented and achieved a very high level of participant satisfaction. This is reflected in: (i) active participant engagement during the sharing session; (ii) increased efforts to develop local alternative food sources, particularly cocoa cultivation, through collaboration with Cau Chocolate in Desa Tua Petiga; and (iii) the identification of village potentials supported by the contribution of the Merah Putih Cooperative through the integration of cocoa cultivation, cocoa-based UMKM and derivative products, educational and agrotourism development, as well as the creation of tourism products and souvenirs.